“Now the Forest Is Over”: Transforming the Commons and Remaking Gender in Cambodia's Uplands - Beban, Alice; Bourke Martignoni, Joanna (Frontiers in Sustainable Food Systems, 2021)
Communal lands and natural resources in rural Cambodia have transformed over the past thirty years as the country attempts to transition from conflict to liberal democracy and integrates into global agricultural value chains. We find that gender relations are changing as a result of land privatization and the ensuing social and ecological crises of production and reproduction. The forest has become a space for the articulation of new masculinities modulated through class and racialised power, while women are increasingly relegated to the private space of the home and village, negotiating expectations that they perform care, farming and food provisioning work while juggling household debt. We ground our argument in a large sample of qualitative interviews conducted between 2016-2020 in the upland provinces of Kampong Thom, Kratie and Ratanakiri that provide narrative accounts of the transformation of common forest and grazing lands, logging livelihoods and food provisioning practices. Using a feminist political ecology perspective, we highlight the contradictory processes of enclosure of the commons, which operate simultaneously as sites of violence, resistance, adaptation and continuity.